2013
DOI: 10.1177/1934578x1300801017
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Xanthine Oxidase-inhibitory Component from Sophora Flavescens using NMR-based Metabolomics

Abstract: We demonstrate that NMR-based metabolomics studies can be used to identify xanthine oxidase-inhibitory compounds in the diethyl ether soluble fraction prepared from a methanolic extract of Sophora flavescens. Loading plot analysis, accompanied by direct comparison of 1 H NMR spectra exhibiting characteristic signals, identified compounds exhibiting inhibitory activity. NMR analysis indicated that these characteristic signals were attributed to flavanones such as sophoraflavanone G and kurarinone. Sophoraflavan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In a previous study, we used methanol (MeOH) to extract samples of Sophora f lavescens Aiton for NMR-based metabolomics analyses. 16 In the present study, MeOH was also used for extraction because it is a highly polar solvent. We prepared a MeOH extract of a lichen sample and then redissolved the dried extract residue with DMSO to an appropriate concentration for MS analysis.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we used methanol (MeOH) to extract samples of Sophora f lavescens Aiton for NMR-based metabolomics analyses. 16 In the present study, MeOH was also used for extraction because it is a highly polar solvent. We prepared a MeOH extract of a lichen sample and then redissolved the dried extract residue with DMSO to an appropriate concentration for MS analysis.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Natural biological samples are ideal materials for use in developing metabolomics methods due to the many constituents they contain. In a previous study, we used methanol (MeOH) to extract samples of Sophora flavescens Aiton for NMR-based metabolomics analyses . In the present study, MeOH was also used for extraction because it is a highly polar solvent.…”
Section: Resultsmentioning
confidence: 99%
“…Xanthine oxidase is an important drug target used for gout, hyperuricemia, ischemic tissue/vascular injuries, inflammation related diseases, and myocardial infarction. Suzuki et al (2013) studied the xanthine oxidase inhibition potential of kurarinone. The result showed that kurarinone was active against the enzyme only at a higher concentration (100 µM) ( Suzuki et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“… Suzuki et al (2013) studied the xanthine oxidase inhibition potential of kurarinone. The result showed that kurarinone was active against the enzyme only at a higher concentration (100 µM) ( Suzuki et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported the use of multivariate analysis, such as PCA with 1 H-NMR data in a chosen range, to analyze the cultivating places or the biological activities of various natural extracts. 4,5) Several other studies have employed 13 C-NMR data and multivariate analysis to distinguish the components of complex mixtures such as soy sauce. 6,7) However, very little experimental work has combined multivariate analysis with 13 C chemical shift data to establish predictive models.…”
Section: Introductionmentioning
confidence: 99%